Values of Prophetic Communication in Syair Gurindam Dua Belas - Putra, Dian Dwi Ok; Husaini, Adian; Saepudin, Didin; Bahrudin, Ending (PT FORMOSA CENDEKIA GLOBAL, 2024)
Poetry is old literature whose message can still be relevant today. This research explores the value of prophetic communication which is a derivative of Kuntowijoyo's Prophetic Social Sciences in poetry entitled Gurindam Dua Belas which contains twelve articles with different themes by Raja Ali Haji who comes from Penyengat Island, Riau Islands Province. This poetry is researched because of its timeless nature. The semiotic principles studied in this paper are the principles of signified, signifier, iconic, and arbitrator which will also be explained in terms of the value of prophetic communication. The value elements of prophetic communication are humanization (amar ma'ruf) which is related to humanizing humans, liberation (nahi munkar) which is related to preventing evil and liberation, and transcendence (tu'minuna billah) which is faith in Allah who returns everything to the Qur'an. 'an and As-Sunnah. Although it does not explicitly mention the verses and surahs in the Koran. In total there are eight articles that fall into the Prophetic Communication category in this poem. Many of the poetry's values ​​contain humanization from a societal perspective, followed by liberation and transcendence.